The Influence of Distance Learning use Lectora Inspire-Based Interactive Learning Media on Students' Mathematical Problem Solving Abilities In Primary Schools - Suryaningrat, Eko Fajar; Nugraha, Widdy Sukma; Asy’ari, Lutfy; Nurjamaludin, Muhammad (Social, Humanities, and Educational Studies (SHES): Conference Series, 2021)
The purpose of this study was to find out how much distance learning use Interactive learning media based on lectora inspire influence on the learning process and Mathematical Problem Solving Abilities. This research uses collaborative research between lecturers, students, and teachers in 2020 at one of the primary schools in west Java.This research was a quasi-experiment research with Pretest-Posttest Control Design. Data collection techniques tests. the result of the research is to find out how the impact of the use of learning media lectora inspire based interactive on students approach is proven to improve Mathematical problem solving abilities in primary schools.The conclusion of research was that there was a difference of effect of distance learning use lectora inspire-based interactive learning media on the Mathematical Problem Solving Abilities of students between control and experiment classes and Students' attention was also more focused so it is easier to concentrate on receiving lessons.